Bagaimana Keluar dari Masalah, Hukum Impoten, Korupsi Omnipoten - Winarta, Frans Hendra (Pelita Harapan University, 2001)
Corruption occurs whenever a judge or court officer seeks or receives a benefit of any Â kind in respect of an exercise of power or other action. Such acts usually constitute criminal offences under national law. Examples of criminal corrupt conduct are : bribery, fraud, utilisation of public resources for private gain, deliberate loss of court records, and deliberate alteration of court records. Corruption also occurs when instead of proceedings being determined on the basis of evidence and the law, their outcome is affected by improper influences, inducements, pressures, threats, or interference or directly or inderectly, from any quarter or for any reason including those arising from : a conflict interest; nepotism; favouritism to friends, or a particular association or institution; consideration of promotional prospects; consideration of post retirement placements; improper socialisation with members of the legal profession, the executive, or the legislature; socialisation with litigants, or prospective litigants; predetermination of an issue involved in the litigation; prejudice; and having regard to the power or desire of goverment or political parties; or other pressure groups. Corruption is so large and nearly all of it happens in Indonesia because the law is impotent. Is there any medicine or is it still posible cured ? It is nothing imposible.Â